Cytotoxic agents are detrimental to bone formed by distraction osteogenesis - Monsell, Fergal P. (Springer Milan, 2013)
Distraction osteogenesis can be used to replace segmental bone loss when treating malignant bone tumors in children and adolescents. These patients often receive cytotoxic chemotherapy as part of their treatment regimen. The effect of cytotoxic drugs on the cellular processes during distraction osteogenesis and the structural and mechanical properties of regenerate bone is unknown. We therefore used a rabbit model of distraction osteogenesis to determine that cytotoxic agents had a detrimental effect on regenerate bone formed by this technique. We administered adriamycin and cisplatinum to 20 rabbits using two different simulated chemotherapy regimens. All rabbits underwent an osteotomy at 12 weeks of age. Distraction osteogenesis began 24 h later at a rate of 0.75 mm a day for 10 days, followed by 18 days without correction to allow for consolidation. Regenerate bone was assessed using plain radiographs, bone densitometry, and mechanical testing. Peri-operative chemotherapy decreased the mechanical properties of the regenerate with regard to yield strain (3.7 × 10(−2) vs. 5.2 × 10(−2)) and energy at yield (2.73 × 10(7) vs. 3.92 × 10(7)). Preoperative chemotherapy in isolation reduced bone mineral density (0.38 vs. 0.5 g/cm(2)), bone mineral content (0.24 vs. 0.36 g), and volumetric bone mineral density (0.57 vs. 0.65 g/cm(2)) with no alterations in the mechanical properties. Conclusions: Preoperative chemotherapy appears to decrease the volume of regenerate bone, without affecting structural integrity, suggesting that the callus formed is of good quality. The converse appears true for peri-operative chemotherapy.